Strategi Komunikasi Organisasi di Internal LSO HWFC dalam Menjaga Motivasi Para Kader - Rangga Dwiekie; Rizki Agus Sallam; Keysza Nurmuzaffar; Hafizh Aulia (MUKASI: Jurnal Ilmu Komunikasi, 2024)
An organization is an association of various people who have the same goals and missions and are structured. However, the existence of different motivations between people in the organization is one of the problems for the effectiveness of communication within the organization. Hizbul Wathon Football Club, Faculty of Social and Political Sciences, University of Muhammadiyah Jakarta, in the process of sustaining the organization, intergroup communication tactics are needed to achieve organizational goals. Therefore, it makes researchers interested in conducting research with the title "Organizational Communication Strategy in Internal LSO HWFC in Maintaining the Motivation of Cadres". The theory used is communication behaviorism by John Broadus Watson, which is all actions or behaviors that include response or reply to a given thing. The results revealed that the Hizbul Wathon Football Club FISIP UMJ has the same strategy as the theory used because the internal Hizbul Wathon Football Club provides what cadres want such as a comfortable ball training environment that causes cadres to feel comfortable and bound by the organization. This research also states that comfortable communication will make cadres motivated to remain in their organizational environment.